Direct Synthesis of Highly Designable Hybrid Metal Hydroxide Nanosheets by Using Tripodal Ligands as One‐Size‐Fits‐All Modifiers. Issue 21 (16th February 2017) - Kuroda, Yoshiyuki; Koichi, Tatsuyuki; Muramatsu, Keisuke; Yamaguchi, Kazuya; Mizuno, Noritaka; Shimojima, Atsushi; Wada, Hiroaki; Kuroda, Kazuyuki
Abstract: Brucite‐type layered metal hydroxides are prepared from diverse metallic elements and have outstanding functions; however, their poor intercalation ability significantly limits their chemical designability and the use of their potentially ultrahigh surface areas and unique properties as two‐dimensional nanosheets. Here, we demonstrate that tripodal ligands (RC(CH2 OH)3, R=NH2, CH2 OH, or NHC2 H4 SO3 H) are useful as "one‐size‐fits‐all" modifiers for the direct synthesis of hybrid metal hydroxide nanosheets with various constituent metallic elements (M=Mg, Mn, Fe, Co, Ni, or Cu) and surface functional groups. The hybrid nanosheets are formed directly from solution phases, and they are stacked into a turbostratic layered structure. The ligands form tridentate Mg‐O‐C bonds with brucite layers. The hybrid brucite intercalates various molecules and is exfoliated into nanosheets at room temperature, although the non‐modified material does not intercalate any molecules. Consequently, both the constituent metallic elements and surface functional groups are freely designed by the direct synthesis. Abstract : One and all : Hybrid metal hydroxide nanosheets are directly synthesized from solutions of metal salts by using tripodal ligands as one‐size‐fits‐all modifiers, despite the poor intercalation abilities of their corresponding layered materials. The hybrid nanosheets are highly designable by replacing the constituent metallic elements and organic functional groups on the layer surface.